The Surface-Exposed Protein SntA Contributes to Complement Evasion in Zoonotic Streptococcus suis - Deng, Simin; Xu, Tong; Fang, Qiong; Yu, Lei; Zhu, Jiaqi; Chen, Long; Liu, Jiahui; Zhou, Rui (Frontiers in Immunology, 2018)
Streptococcus suis is an emerging zoonotic pathogen causing streptococcal toxic shock like syndrome (STSLS), meningitis, septicemia and even sudden death in human and pigs. Serious septicemia indicates this bacterium can evade the host complement surveillance. In our previous study, a functionally unknown protein SntA of S. suis has been identified as a heme-binding protein, and contributes to virulence in pigs. SntA can interact with the host antioxidant protein AOP2 and consequently inhibit its antioxidant activity. In the present study, SntA is identified as a cell wall anchored protein that functions as an important player in S. suis complement evasion. The C3 deposition and membrane attack complex (MAC) formation on the surface of sntA-deleted mutant strain ΔsntA are demonstrated to be significantly higher than the parental strain SC-19 and the complementary strain CΔsntA. The abilities of anti-phagocytosis, survival in blood, and in vivo colonization of ΔsntA are obviously reduced. SntA can interact with C1q and inhibit hemolytic activity via the classical pathway. Complement activation assays reveal that SntA can also directly activate classical and lectin pathways, resulting in complement consumption. These two complement evasion strategies may be crucial for the pathogenesis of this zoonotic pathogen. Concerning that SntA is a bifunctional 2’, 3’-cyclic nucleotide2’-phosphodiesterase/3’-nucleotidase in many species of Gram-positive bacteria, these complement evasion strategies may have common biological significance.